2016
DOI: 10.4103/0971-5916.195035
|View full text |Cite
|
Sign up to set email alerts
|

Derivation & validation of glycosylated haemoglobin (HbA1c) cut-off value as a diagnostic test for type 2 diabetes in south Indian population

Abstract: Background & Objectives:Glycosylated haemoglobin (HbA1c) has been in use for more than a decade, as a diagnostic test for type 2 diabetes. Validity of HbA1c needs to be established in the ethnic population in which it is intended to be used. The objective of this study was to derive and validate a HbA1c cut-off value for the diagnosis of type 2 diabetes in the ethnic population of Rayalaseema area of south India.Methods:In this cross-sectional study, consecutive patients suspected to have type 2 diabetes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…In our study 2 the Youden's Index was 0.75; the HbA 1c cut-off that provided such index was >6.3; both (0,1) approach and the Youden's Index provided the same cut-off. As a note of caution we feel that any recommendations that arise from simulated data with various prevalence and cost assumptions should also be given consideration in addition to data (study) driven recommendations alone.…”
supporting
confidence: 47%
See 3 more Smart Citations
“…In our study 2 the Youden's Index was 0.75; the HbA 1c cut-off that provided such index was >6.3; both (0,1) approach and the Youden's Index provided the same cut-off. As a note of caution we feel that any recommendations that arise from simulated data with various prevalence and cost assumptions should also be given consideration in addition to data (study) driven recommendations alone.…”
supporting
confidence: 47%
“…We read the correspondence by Habibzadeh et al 1 on our article 2 with great interest. They stated that Perkins and Schisterman 3 , in their article clearly recommended the use of the Youden's index (Se + Sp – 1) and warned about using the minimum distance criterion.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…HbA1c >6.3% was found to be optimal cutoff value for the diagnosis of type 2 diabetes in a study from Andhra Pradesh state in South India. [ 27 ] A study from North India[ 6 ] found an optimal HbA1c cut-point of 6.1% for diabetes screening and HbA1c of 6.5% had optimal specificity for diabetes diagnosis. Optimal HbA1c cutoff for prediabetes diagnosis in the present study was 5.9%, with a much lower accuracy compared to diabetes diagnosis.…”
Section: Discussionmentioning
confidence: 99%